Computer networks. A top-down approach featuring Internet, second edition : James F. Kurose. Pearson Educación (Addison Wesley), 2004 - López, Ricardo A. (2007)
The book is intended to be used in an introductory and intermediate level course on computer networks, both whitin Computer Science and Electric Engineering scopes. One of its characteristics is that the entire research software is presented in Java, but with such simplicity that a student with basic knowledge of C or C++, would not have any difficulty in the analysis of the presented examples. One of the main differences of this book with respect to those dealing with similar topics is its top-down approach. That is, the description of computer networks begins with the model application layer, descending towards the conclusion at the physical layer. This is particularly interesting because the students begins with the identification of objects that are tangible in their daily lives, such as e-mail or the WEB, and from there they move downwards to a more detailed view of the network performance supporting these applications.